Screening of Lactic Acid Bacteria Isolated from Fermented Cowpea and Optimization of Biomass Production Conditions - Hong Xu; Danyang Li; Xue Jiang; Qi Pei; Zhengqin Li; Philippe Madjirebaye; Mingyong Xie; Tao Xiong; Zhanggen Liu (Foods)
Considering the four characteristics of strains, including acid production, acid tolerance, salt tolerance, and nitrite degradation rate, Pediococcus pentosaceus NCU006063 was selected as the fermentation agent, and the medium composition of Pediococcus pentosaceus NCU006063 was optimized using Plackett–Burman and central composite rotational design. Three of the seven factors studied in the Plackett–Burman design significantly affected the viable counts. A central composite rotational design was used to optimize the significant factors and generate response surface plots. Using these response surface plots and point predictions, the optimal factors were soy peptone (38.75 g/L), FeSO4 (0.10 g/L), and VB7 (20 g/L). In addition, the optimized incubation conditions were a temperature of 39 °C, an initial pH value of 7, and an inoculation volume of 3%. The optimized biomass production parameters were a constant pH (6.5), neutralizing agent types (25% NH3·H2O), and gas types (N2). Under these optimal conditions, Pediococcus pentosaceus NCU006063 exhibited a great viable bacterial count of up to 2.65 × 1010 CFU/mL, which is 9.71 times higher than that of MRS broth (2.73 × 109 CFU/mL). These results demonstrated that the Pediococcus pentosaceus NCU006063 strain has excellent potential as a fermentation agent and can provide a theoretical base for the in-depth exploration and promotion of fermented cowpea use in human diets.